(untitled) (World Economics and Finance Bulletin, 2024)
The study aimed to clarify the relationship between electronic management in its dimensions (human resources, technical and security, administrative and financial) on administrative performance in its dimensions (organizational dimension, social dimension, strategic dimension, economic dimension). To conduct this study, we implemented a methodology centered on careful observation and interpretation of data. The dataset was collected via a questionnaire designed specifically for this study, drawing from scientific references and previous research. The study sample was comprehensive, as the study community was the Salah Al-Din Education Directorate, and the study included department managers, divisions, and administrative units in the directorate’s office, totaling (110), where the questionnaire was distributed to them, and (105) were retrieved, of which (100) were valid for statistical analysis only. The researcher used the SPSS program to analyze the data, and analysis of the results indicated a substantial effect, in statistical terms, of implementing electronic management systems on administrative performance at a confidence threshold of less than 5%. The study recommended expanding the adoption and use of electronic management in all administrative processes, enhancing the infrastructure of technologies and technology in the organization, and promoting the strategic use of technology to aggregate and evaluate data, yielding actionable insights that support more effective decision-making processes and accurate strategic planning